2022-RA-1318-ESGO Immunohistochemical profiling of macrophage subtypes in the microenvironment of ovarian tumours in young women. (20th October 2022) - Fox, Emily Miranda; Rice, Kirstie; Bhatnagar, Anjali; Kearns, Daniel; Berditchevski, Fedor; Shaaban, Abeer M; El-Ghobashy, Alaa
Abstract : Introduction/Background: Ovarian cancer is a common malignancy associated with poor outcomes. The tumour microenvironment (TME) has been shown to be important in tumorigenesis and prognosis. Tumour associated macrophages (TAM) are the most abundant type of immune cells in TME. Dependent on stimuli, TAM may become anti-tumorigenic M1-type or pro-tumorigenic M2-type (CD163 + ). The significance of TAM in young women with ovarian tumours has not been previously established. We aimed to characterise the TAM in the TME of both borderline (BOT) and malignant ovarian tumours in young women. Methodology: Patients under the age of 50, who underwent surgical management for borderline or malignant ovarian tumours at a large tertiary UK institution in 2010–2015 were included. Full clinical, pathological and outcome data were collected. Primary tumour sections were reviewed and immunohistochemically stained. intra-tumoral and stromal CD68 + /CD163 + cells were scored following the International Immuno-Oncology Biomarker Working Group guidelines. Percentage stromal infiltration was calculated in relation to the stromal area and mean cell count and percentage infiltration per case calculated. Results: 57 patients; 23 with BOT and 24 cancers, were included. The mean age was 38 years, and the commonest histological type was serous carcinoma (n=21). Intra-tumoral CD68 and CD163 were highly significantly expressed in cancers compared with BOT (p<0.001 and 0.004 respectively). Similarly, stromal CD163 mean count and percentage were more abundant in malignant tumours (p=0.03 and 0.02). Mean stromal CD68 count and percentage correlated positively with mean CD163 stromal count and percentage (p=0.02). Risk of malignancy index was a significant predictor of ovarian cancer diagnosis (p=0.04). 15 cancer patients died of the disease. There was no significant association between TAM expression and patient survival. Conclusion: TAM subtypes analysis in ovarian neoplasia of young women confirms higher expression in malignant compared with borderline ovarian tumours. This might have implications on their pathogenesis and management.